Hubungan Antara Motivasi Berprestasi dengan Kinerja Guru yang Sudah Disertifikasi - Ratnasari, Arum Dyah; , Achmad Dwiyanto, S.Psi,. M.Psi (2017)
The government held a certification program that is given to theacers,with the aim to improve the performance of eachers, high teacher performance is expected to improve the quality of education in Indonesia. But apparently the rcertification program admiinistration has not been able to improve the performance of teachers. The aims of the research is to know correlation between achievement motivation and performance of teachers certification. This study uses nirepopulation of teachers certification in Junior High Schoool at Batang, which numbered 80 teachers were used as samples. Sampling using purposive sampling. The research method quantitative approach to teacher performance measurement tools umentation and achievement motivation scale. Data analysis technique using Pearson Product Moment. Based on the analysis of data obtained by the correlation coefficient r = 0.095 with significance = 0.400 (p > 0.05), which means there is no relationship between achievement motivation and performance of teachers certification. Performance relationshipvariables included in both categories, while the achievement otivation variables included in the high category.KeywordsP erformance, teacher certification, achievement motivation